1974
DOI: 10.1126/science.185.4146.169
|View full text |Cite
|
Sign up to set email alerts
|

Mercury's Surface: Preliminary Description and Interpretation from Mariner 10 Pictures

Abstract: The surface morphology and optical properties of Mercury resemble those of the moon in remarkable detail and record a very similar sequence of events. Chemical and mineralogical similarity of the outer layers of Mercury and the moon is implied; Mercury is probably a differentiated planet with a large iron-rich core. Differentiation is inferred to have occurred very early. No evidence of atmospheric modification of landforms has been found. Large-scale scarps and ridges unlike lunar or martian features may refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 17 publications
4
78
1
Order By: Relevance
“…Guest (1975, p. 2463) defined the ICP as 'level to gently rolling ground between and around large craters and basins' (Figure 4). This is the most widespread unit on Mercury and is thought to be the remnants of volcanic flows by most authors Kiefer & Murray, 1987;Murray et al, 1974Murray et al, , 1975Spudis & Guest, 1988;Strom, 1977;Whitten, Head, Denevi, & Solomon, 2014). The emplacement of ICP predates the end of the Late Heavy Bombardment (e.g.…”
Section: Mapped Geologic Provincesmentioning
confidence: 99%
“…Guest (1975, p. 2463) defined the ICP as 'level to gently rolling ground between and around large craters and basins' (Figure 4). This is the most widespread unit on Mercury and is thought to be the remnants of volcanic flows by most authors Kiefer & Murray, 1987;Murray et al, 1974Murray et al, , 1975Spudis & Guest, 1988;Strom, 1977;Whitten, Head, Denevi, & Solomon, 2014). The emplacement of ICP predates the end of the Late Heavy Bombardment (e.g.…”
Section: Mapped Geologic Provincesmentioning
confidence: 99%
“…(Murray et al, 1974b;Strom et al, 1975). From the morphology and dimensions of these scarps and from their transection relationships, the features have been interpreted as thrust faults indicative of planetwide compressive stresses.…”
Section: Is There a Core?mentioning
confidence: 99%
“…The compressive stage in Mercury's history apparently began at least by the end of the period of heavy bombardment of the surface and continued after the later ( but perhaps overlapping) period of emplacement of the smooth plains, thought to be of volcanic origin . Both L Murray et al (1974b) and Strom et al, (1975) speculate that the planetary compression may be the result of core s,irinkage.…”
Section: Is There a Core?mentioning
confidence: 99%
“…Optical searches within a radius of at least 150 000 km from Mercury (corresponding to 4 at maximal elongation from the Sun) are thus motivated and should be able to detect objects of 1 km size or smaller. A search for mercurian satellites on Mariner 10 images has shown that the existence of objects larger than 5 km within 30 Hermeocentric radii is improbable (Murray et al 1974).…”
Section: Discussionmentioning
confidence: 99%